PRICKLE1‐related early onset epileptic encephalopathy. Issue 12 (22nd October 2018) - Mastrangelo, Mario; Tolve, Manuela; Martinelli, Martina; Di Noia, Sofia P.; Parrini, Elena; Leuzzi, Vincenzo
Abstract : The PRICKLE1 (Prickle Planar Cell Polarity Protein 1‐MIM 608500) gene is involved in different phases of human development. The related diseases include autosomal recessive progressive myoclonus epilepsy ‐ ataxia syndrome, neural tube defects associated with heterozygous mutations, agenesis of corpus callosum, polymicrogyria, and autistic spectrum disorder. Reported here is a young boy with a new variant (NM_153026.2:c.820G>A, p.Ala274Thr) presenting with an early infantile epileptic encephalopathy with developmental arrest.